MODEL EFEKTIVITAS PEMBERDAYAAN PEREKONOMIAN MASYARAKAT DENGAN PERAN PEMERINTAH MENGAKOMODASI HOBI/MINAT DAN BAKAT MASYARAKAT - Eddi Indro Asmoro (Jurnal Ilmiah Dinamika Teknik, 2014)
Appointment of value from community hobbies/interests and talents with the goverment role of facilitator, regulator, and a catalyst is new hope community empowerment. Community of society is proper as the basic ideas of alternative community economic empowerment. Impact of the role of government policy is believed to be very outstanding researchers and would bring the creativity of all lines of business community. Extraordinary impact that is believed to researchers need scientifically studies with reference to empirical studies. Impact is the result of the interaction of interdependent communities (give and take). This study will design a concept model with structural approach equotion modeling (SEM). Impact on the value of the interaction of interrelated system will provide added value of an idea of value chain that will happen and be continuous improvement. Expectations of this study is to determine the endogenous constructs and operational indicators. Community empowerment of value hobbies/interests and talents will be examined from a variety of disciplines to obtain the results of the study broadly. This facilitates further research in the stand point for the alleviation and economic development for the community to understand the interaction of the system. Key words: Hobbies and Talents, Interaction, Value Chain, Added Value, Empowerment